Not all that Glitters is Gold: ICT and Inclusive Human Development in Sub-Saharan Africa - Simplice Asongu; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2016)
This paper examines the short and long term effects of information and communication technology (ICT) on inclusive human development in a panel of 49 Sub-Saharan African countries for the period 2000-2012. ICT is measured in terms of mobile phone penetration, internet penetration and telephone penetration rates. While mobile phone penetration has positive short run and long term effects on inclusive human development, the effects of internet and telephone penetrations are insignificant. Moreover, the long term inclusive human development benefits of the mobile phone are higher than the corresponding short term rewards. Policy implications are discussed.
Keywords: G20; I10; I32; O40; O55; 330; ICT; inclusive human development; Africa